The Impact of the External Auditor’s low fees on the quality of Professional Performance in Saudi Arabia - Mohamed, Fatima Elyass (Advances in Social Sciences Research Journal, 2020)
This study was conducted to study the impact of low fees of the external auditors on the quality of the professional performance in the Kingdom of Saudi Arabia including the stages of development of the external audit, the standards of quality control, the factors affecting the quality of performance and the matters that affect the fees of the external auditor. The importance of this research stems from the importance of the auditor's work and how the events of economic collapses affect the fees of the auditor. This research raised several questions about the factors affecting improving the quality of audit services, the extent of the impact of the independence of the audit work team and determining their fees on the quality of the review process and determining the relationship between the internal auditor and the external auditor and the extent of approval of the second over first. The study samples were randomly selected to be about 10% of the study community (15 offices). Sixty questionnaires were distributed, of which 45 returned questionnaires, 75% valid for analysis. Data were analyzed using SPSS software for descriptive statistical analysis. The tested hypothesis were as follow: professional performance quality is not affected by the evolution of the audit office; It does not affect low fees and low on quality performance; whenever the level of fees dropped the more professional level of excesses and the higher the quality of the performance of the internal auditor, the less external work references. The assumptions were tested regarding the above group of factors or the effect of the independent variables on the dependent variable. All of them accepted the hypothesis that the quality of professional performance was not affected by the development of the audit offices fees.